The use of documentary heritage for Primary and Secondary Education: educational workshops in historical archives - Ortega Cervigón, José Ignacio (Clio. History and History Teaching, 2021)
The essential objective of the study is to promote the use of documents and primary sources kept by the archives as valid elements to formulate hypotheses about the construction of historical knowledge. The investigation shows the need to combine the use of primary sources and the didactic contribution of archives to value the documentary heritage in History education. The main results synthesize the realization of different educational workshops adapted to different academic levels in historical archives, with the development of activities and their evaluation. The conclusions confirm students have obtained knowledge about the daily life of social groups and acquired some basic didactic concepts such as multi-causality, change and the continuity of historical time.